Cultural Heritage Preservation Is Vital for Maintaining Societal Identity, And Promoting CrossCultural Understanding - Akramova Kamola Akramovna (Academia One Publishing, 2024)
This article highlights the significance of cultural heritage preservation and the necessity for collective action: Threats such as natural disasters, urbanization, and globalization necessitate collaborative efforts from governments, NGOs, and communities. Successful conservation initiatives, such as the restoration of iconic landmarks, demonstrate the effectiveness of collective action in safeguarding cultural heritage. Education and awareness-raising play crucial roles in instilling a sense of responsibility and stewardship towards cultural heritage. As custodians of our shared cultural legacy, individuals and institutions must actively participate in preserving and promoting cultural heritage for future generations.
Keywords: Tangible Cultural Heritage; Intangible Cultural Heritage; Artifacts